2022
DOI: 10.26714/nm.v3i2.8302
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan slow deep breathing dan dzikir terhadap tingkat kecemasan penderita hipertensi pada lansia

Abstract: Hipertensi adalah keadaan dimana terjadinya peningkatan tekanan darah diatas batas normal. Batasan pada lansia yang berusia diatas 60 tahun bila sudah lebih dari 140/90 mmHg.Kondisi tubuh lansia yang mengalami hipertensi dapat kembali membaik,akan tetapi faktor-faktor psikologis lansia sangat berpengaruh terhadap proses penanganan masalah hipertensi.Hal ini dapat menyebabkan lansia mengalami gangguan psikis seperti kecemasan. Penanganan kecemasan dapat dilakukan dengan jenis piskoterapi yaitu dengan slow deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
3
0
0
1
Order By: Relevance
“…According to the study's findings in RW 03 Limbangan Village, 31 of the 40 respondents (or 77.5%) reported mild anxiety, and 9 respondents (or 22.5%) had moderate anxiety. This study is consistent with research (Putri, Nabilla Sholikhah, 2021) in which moderate anxiety (11.5%) was experienced by moderately 85 respondents (88.5%). Aging elements and the body's aging process contribute to anxiety.…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the study's findings in RW 03 Limbangan Village, 31 of the 40 respondents (or 77.5%) reported mild anxiety, and 9 respondents (or 22.5%) had moderate anxiety. This study is consistent with research (Putri, Nabilla Sholikhah, 2021) in which moderate anxiety (11.5%) was experienced by moderately 85 respondents (88.5%). Aging elements and the body's aging process contribute to anxiety.…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
“…According to this study, older women are more likely than males to acquire hypertension. The findings of this survey are consistent with studies by (Putri, Nabilla Sholikhah, 2021), which found that there are more women than men in Indonesia. The findings of this study are also consistent with studies from (Nasrani & Susi, 2015), which explains that women experience a higher incidence of hypertension because their levels of the hormone estrogen decline as they age, making them more vulnerable to the condition.…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
“…This study shows that women are more at risk of developing hypertension than men. The results of this study are in line with research conducted by (Putri, Nabilla Sholikhah, 2021) that the female population in Indonesia is greater than the male population. The results of this study are also in line with research from (Nasrani & Susi, 2015) which explains that the incidence of hypertension is more suffered by women due to a decrease in the hormone estrogen when entering old age, so that they are more susceptible to hypertension.…”
Section: Characteristics Of Respondents Gendersupporting
confidence: 91%
“…Penyakit jantung koroner dengan tambahan penyakit penyerta menyebabkan masalah kematian nomor satu di dunia, penyakit jantung koroner yang disebut penyakit kronis dengan penyakit lainnya seperti hipertensi, tukak lambung, diabetes melitus, gagal ginjal, dyspepsia fungsional, gagal jantung, dan aritmia dapat muncul dan ada pada manusia yang mengharuskan dokter meresepkan obat dengan jumlah yang banyak. Keadaan jantung koroner secara tiba-tiba, sebenarnya sudah melewati proses yang cukup lama yang dimulai dengan adanya masalah pada pembulu darah (arteriosclerosis) yang mengakibatkan jantung kekurangan pemasokan darah ke otot jantung [7]. Penelitian ini bertujuan untuk mengetahui potensi interaksi obat yang diberikan pada pasien yang menderita penyakit jantung koroner (PJK) dengan tambahan penyakit penyerta di poliklinik Rumah Sakit I.A.…”
Section: Pendahuluanunclassified